Performance structure analysis of the men`s and women`s badminton doubles matches in the Olympic Games from 2008 to 2016 during playoffs stage - Abián-Vicén, J.; Sánchez, L.; Abián, P. (International Journal of Performance Analysis in Sport, 2018)
The purpose was to compare the timing factors of top world-level badminton in men`s and women`s doubles matches in the Olympic Games in Beijing, London and Rio to observe the evolution of this sport between 2008 and 2016. All the matches from the quarterfinals to the final of the men`s and women`s doubles events from the 2008, 2012 and 2016 Olympic Games were analysed (48 matches). The matches were retrieved from the Olympic Multimedia Library. Higher values in match duration, real time played, total points played, shots per match and rest time between points were found in Rio than Beijing and London (P < 0.05). The real time played, percentage of time played, shots per rally, rally time and work density were higher and shot frequency was lower in the women`s doubles event than the men`s doubles event (P < 0.05) in all the Olympics analysed. In conclusion, Badminton in the men`s and women`s doubles events evolved from 2008 to 2016 towards longer matches with greater rest intervals. The evolution has been similar in the men`s and women`s doubles; the women`s doubles showed longer points with greater real time in the matches, while the men`s doubles showed greater intensity.